Mengembangkan Desain Pelatihan Untuk Meningkatkan Kompetensi Guru Dalam Mengimplementasikan Kurikulum Pendidikan Nilai CHBYK - Matias Sira Leter; R Riswandi; H Herpratiwi (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
The purpose of this study was to design training to improve teacher competence in implementing the CHYBK value education curriculum at YLM for elementary school teachers who teach at several YLM elementary schools in Lampung and Palembang and to review the effectiveness of the training design developed. This type of research uses the method and development (R & D) with the ADDIE development model. The population is all teachers who teach at SD Xaverius 1 Bandar Lampung, SD Xaverius Metro, and SD Xaverius 1 Palembang with a total of 103 teachers and the sample for testing the product of the results of development is 52 teachers. Data was collected using observation, survey, and pretest-posttest techniques. The data analysis technique was carried out by descriptive analysis including product feasibility analysis, product attractiveness analysis and teacher competency level analysis. The results of the study indicate that the product developed is feasible and attractive and can increase teacher competence.